Differential roles for cortical versus sub-cortical noradrenaline and modulation of impulsivity in the rat - Benn, A; Robinson, E (Springer Verlag, 2016)
Rationale Atomoxetine is a noradrenaline re-uptake inhibitor licensed for the treatment of adult and childhood attention deficit hyperactivity disorder. Although atomoxetine has established efficacy, the mechanisms which mediate its effects are not well understood. Objectives In this study, we investigated the role of cortical versus sub-cortical noradrenaline by using focal dopamine beta hydroxylase-saporin-induced lesions, to the prefrontal cortex (n = 16) or nucleus accumbens shell (n = 18). Methods Healthy animals were tested by using the forced-choice serial reaction time task to assess the impact of the lesion on baseline performance and the response to atomoxetine and the psychostimulant amphetamine. Results We observed attenuation in the efficacy of atomoxetine in animals with lesions to the nucleus accumbens shell, but not the prefrontal cortex. Amphetamine-induced increases in premature responses were potentiated in animals with lesions to the prefrontal cortex, but not the nucleus accumbens shell. Conclusions These data suggest that noradrenaline in the nucleus accumbens shell plays an important role in the effects of atomoxetine. Under these conditions, prefrontal cortex noradrenaline did not appear to contribute to atomoxetine’s effects suggesting a lack of cortical-mediated “top-down” modulation. Noradrenaline in the prefrontal cortex appears to contribute to the modulation of impulsive responding in amphetamine-treated animals, with a loss of noradrenaline associated with potentiation of its effects. These data demonstrate a potential dissociation between cortical and sub-cortical noradrenergic mechanisms and impulse control in terms of the actions of atomoxetine and amphetamine.